AB1058 Time to resolution of tophi with urate lowering agents: A literature analysis of randomized trials. (23rd January 2014) - Becker, M.; Yood, R.; Perez-Ruiz, F.; Dalbeth, N.
Abstract : Background: The tophus is a pathognomonic feature of chronic gout and may cause disability and joint damage. Accordingly, OMERACT has endorsed tophus measurement as a key domain in clinical trials of chronic gout. The approval of febuxostat (FEB) in 2009 and pegloticase (PGL) in 2010 has been accompanied by publications describing clinical trials of urate-lowering therapies (ULTs). These trials also provide detailed data, not previously available, on change in tophus burden in response to treatment in defined gout populations. Objectives: We compared tophus resolution in published clinical trials of ULTs that included such measurements. Methods: A PubMed search using the terms "gout" and "tophi OR tophus" was performed with the following limits applied: clinical trial, humans, and English. The 15 articles retrieved were evaluated for appropriateness and used to identify additional publications/abstracts. Six trials met the analysis criteria. Results: Conclusions: Clinical trials of ULTs have not used consistent methods or timepoints to evaluate tophus response. Nevertheless, pegloticase treatment results in more robust and rapid resolution of tophi compared to treatment with febuxostat or allopurinol. References: Wallace et al. Arth Rheum 1977;20:895-900. Disclosure of Interest: M. Becker Grant/Research support from: Savient, Takeda, Consultant for: Savient, Takeda, Ardea, BioCryst, Regeneron, URL/Mutual/Metabolex/Chugai, R. Yood Grant/Research support from: Savient, Takeda, F. Perez-Ruiz Consultant for: Ardea, Menarini, Novartis, Savient, Speakers Bureau: Ardea, Menarini, Novartis, Savient, N. Dalbeth Grant/Research support from: Fonterra, Consultant for: Takeda, Ardea, Novartis, Abbott, Roche